Transport and climate change - Ryley, Tim; Chapman, Lee, 1977- (Emerald, 2012)
This topical volume covers the intersection between transport and climate change, with papers from the 'Transport & Climate Change' session of the RGS-IBG conference in London, September 2010. It considers the role of transport modes at varying spatial dimensions and a range of perspectives on the relationship between transport and climate change.
Keywords: Transportation.; Transportation and state.; Transportation -- Environmental aspects.; Climatic changes -- Economic aspects.; elektronické knihy; electronic books